Pengaruh Word Of Mouth dan Media Sosial Tiktok Terhadap Keputusan Pembelian Wedding Organizer Yasiah Make-Up - Yulia, Nova; Nurlenawati, Netti; Triadinda, Dexi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The service industry, including wedding organizer services, is experiencing rapid growth. This study examines the influence of Word of Mouth and TikTok social media on consumer decisions in choosing Yasiah Make-up services. With a quantitative approach and 96 respondents selected purposively, the data were analyzed using multiple linear regression through SPSS version 24. The results showed that both variables had a significant effect, both partially and simultaneously, with TikTok social media having a greater influence. In conclusion, the synergy between Word of Mouth and TikTok social media is important in marketing strategies. Therefore, Yasiah Make-up is advised to manage testimonials and utilize TikTok creative content optimally.